Effects of COVID-19 pandemic period on neonatal mortality and morbidity - Berna Hekimoğlu; Filiz Aktürk Acar (Elsevier, 2022)
Background: Corona Virus Disease 2019 (COVID-19) in pregnant women has important impacts on perinatal and neonatal outcomes. However, there are a limited number of studies investigating the effect of the pandemic period on newborns. With this study, we aimed to determine the impact of the 2020 COVID-19 outbreak on prenatal care, obstetric outcomes, neonatal mortality and morbidity. Methods: The retrospective results of patients hospitalized to the Tertiary Neonatal Intensive Care Unit between 1 March and 30 May 2020, the first peak period of the pandemic in our country, were compared with the data of the same period of the previous year. Results: A total of 307 cases were included in our study. The mean gestational weeks of the neonates hospitalized in the Neonatal Intensive Care Unit during the COVID-19 period were higher than those in the control group (p: 0.003). During the pandemic period, an increase was found in the frequency of pregnant women presenting to obstetric emergency services in emergencies requiring acute intervention (p: 0.01). Compared to the control group, there was an increase in the number of infants with small for gestational age (SGA) diagnosis, 5th-minute Apgar score of <7, and newborns with a diagnosis of hypoxic-ischemic encephalopathy who were treated with hypothermia in the study group (p < 0.05). No difference was found in terms of maternal and neonatal mortality (p > 0.05). Conclusions: During the COVID-19 pandemic, it was shown that pregnant women disrupted their regular antenatal care, and more pregnant women were admitted to the obstetric emergency department with emergencies requiring acute intervention. This led to an increase in the number of cases diagnosed with SGA and hypoxic-ischemic encephalopathy in newborns. Our results will be useful for better management of current and future pandemic periods.